Kanglaite Combined With Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitor Therapy for Stage III/IV Non-Small Cell Lung Cancer: A PRISMA-Compliant Meta-Analysis - Kong, Fanming; Wang, Chaoran; Li, Xiaojiang; Jia, Yingjie (Frontiers in Pharmacology, 2021)
Objective: Kanglaite(KLT), a type of Chinese medicine preparation, is considered as an adjuvant therapy option for malignant cancer treatment. This study aimed to systematically investigate the efficacy and safety of the combination of KLT and EGFR-TKI for the treatment of stage III/IV non-small cell lung cancer. Methods: Randomized controlled trials (RCTs) comparing KLT plus EGFR-TKI with EGFR-TKI alone for stage III/IV non-small cell lung cancer. Literature searches (up to July 10, 2021) were performed using the PubMed, Web of Science, Cochrane Library, EMBASE, ClinicalTrials.gov, China National Knowledge Infrastructure (CNKI), Wanfang Databases, Chinese Scientific Journal Database (VIP). Two researchers independently assessed the risk of bias with the tool of Cochrane Collaboration. RevMan 5.3.0 was used in analyzing included trial data. Results: 12 RCTs recruiting 1046 patients with stage III/IV NSCLC were included. Results showed that compared with EGFR-TKI alone, KLT plus EGFR-TKI can improved DCR (OR=3.26;95% CI:2.22-4.77;P< 0.00001), ORR(OR=2.59; 95% CI: 1.87-3.58; p< 0.00001), KPS (OR=2.76, 95% CI:1.73-4.39;P<0.00001), CD4+T cells (WMD=5.36; 95%CI:3.60-7.13; P<0.00001), the CD4+/CD8+ ratio (WMD = 0.18; 95% CI: 0.08-0.27; P =0.004), NK cells(WMD =4.84; 95% CI: 3.66-6.02; P< 0.00001) and reduced nausea and vomiting(OR=0.37;95%CI:0.16-0.86;P=0.02). Conclusion: KLT plus EGFR-TKI is effective in treating stage III/IV non-small cell lung cancer, its application is worth promoting. Additional double-blind, and multicenter RCTs are required to confirm the efficacy and safety of this treatment.